A Study on The Implementation of Flashcards in Teaching Vocabulary - Fikriani Fikriani; Konder Manurung; Andi Patmasari; Mochtar Marhum (MASI Mandiri Edukasi, 2026)
The objectives of this research are to describe how flashcards are implemented in vocabulary instruction and how students learn vocabulary through their use. This research applied a qualitative design by using a library research method. The data sources were obtained from libraries and online academic databases. The data were analyzed using content analysis, which involved identifying, categorizing, and describing the information from the selected studies. The six previous studies analyzed in this research were conducted by Yusriadi (2021), Mita Agustina Hediyati (2021), Widya Astuti (2022), Fitri Harianingsih (2023), Lisa Febrianti (2024), and Yudit Ba’dung (2024). The results of the data analysis showed that flashcards were used in various ways depending on students’ levels, classroom conditions, and the research design. Generally, the teaching procedures involved introducing vocabulary using flashcards, explaining word meanings through pictures, practicing pronunciation, and reinforcing learning through drilling and repetition activities. The findings revealed that students learned vocabulary effectively through flashcards. Flashcards helped students understand vocabulary more easily through visual media, improve pronunciation through repetition, and remember vocabulary through continuous practice. In quantitative studies, students showed improvement in vocabulary mastery, as indicated by higher post-test scores than pre-test scores, while in qualitative studies, students demonstrated greater engagement, motivation, and understanding of vocabulary. Overall, this study concludes that flashcards are an effective medium that supports both teaching and learning in vocabulary instruction.